Discretion: Whether and How Does It Promote Street-Level Bureaucrats' Taking Charge Behavior? - Yuan, Shuai; Chen, Zhixia; Sun, Mei (Frontiers in Psychology, 2022)
The extant pieces of literature on discretion has mainly focused on its effect on policy implementation and public service delivery, but few studies have looked at its influence on street-level bureaucrats' work behavior, such as taking charge behavior (TCB), which is of great importance for government reforms, especially in developing and transitional countries. Based on the self-determination theory, this study examines whether and how discretion promotes street-level bureaucrats' TCB. Two studies were conducted among street-level bureaucrats in China. First, a survey experiment (n = 355) suggests that discretion positively predicts street-level bureaucrats' TCB. Then, a survey questionnaire study (n = 442) shows that discretion is positively related to TCB through the mediator of public service motivation (PSM). We concluded with implications for theory and practice.